CHARACTER BUILDING FOR STUDENTS THROUGH THE “REHAB HATI” PROGRAM AT GORONTALO PUBLIC JUNIOR HIGH SCHOOL NO. 4 - Syarif K Moito; Sastro M. Wantu; Udin Hamim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Various educational policies have positioned character development as a primary goal that schools must achieve alongside academic achievement. However, various phenomena in the educational environment indicate that mastery of knowledge does not always go hand in hand with the development of positive student behavior. These conditions prompted SMP Negeri 4 Gorontalo to develop the “Rehab Hati” Program as a form of intensive guidance for students with a history of behavioral problems. This study aims to analyze the implementation of the “Rehab Hati” Program, identify the roles of the parties involved in its implementation, and examine changes in students’ character after participating in the program. This study employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, guidance and counseling teachers, homeroom teachers, students participating in the program, and external parties involved in the implementation of the “Rehab Hati” Program. The data were analyzed using an interactive analysis model. The results indicate that the “Rehab Hati” Program is implemented through rehabilitative and collaborative guidance involving various stakeholders. This program contributes to changes in students’ character, particularly in the areas of discipline, responsibility, politeness, and self-control, although the changes demonstrated by each student are not entirely the same. The research findings confirm that character development for students experiencing behavioral problems requires a humanistic, collaborative, and sustainable approach.